2014
DOI: 10.1590/0103-8478cr20131178
|View full text |Cite
|
Sign up to set email alerts
|

Consumer attitude regarding products containing probiotics

Abstract: This study sought to determine the attitude of consumers in the city of Viçosa-MG, Brazil in relation to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
1
3
0
2
Order By: Relevance
“…In the present study, 50% of the athletes rarely or never consumed sauerkraut. In another study with university students, yogurt was the product consumed most frequently by respondents, 3.70% of them reported that they consume the product every day and 27.80% said they consume it at least once a week [35]. In the current study, most of the athletes consume fresh cheese daily.…”
Section: The Frequency Of Consumption Of Probiotics and Fermented Foodssupporting
confidence: 44%
“…In the present study, 50% of the athletes rarely or never consumed sauerkraut. In another study with university students, yogurt was the product consumed most frequently by respondents, 3.70% of them reported that they consume the product every day and 27.80% said they consume it at least once a week [35]. In the current study, most of the athletes consume fresh cheese daily.…”
Section: The Frequency Of Consumption Of Probiotics and Fermented Foodssupporting
confidence: 44%
“…The most common reasons of usage among the respondents were to mitigate the side effects of previous antibiotic treatment and the symptoms of diarrhoea. Although in the literature the most cited reason of probiotic use was also antibiotic treatment, other promoter factors were mentioned in a great number as well, such as oralhealth, the maintenance of gut flora, cardiovascular health, and immune health, which were chosen by the participants of our study as well, but not in a large proportion [5][6][7]10]. This difference may be explained with the relevant Hungarian commercials.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the non-users would be willing to try out these goods if their physician advised them [7]. The majority of the respondents consumed them as food products (yoghurt, fermented milk), while the tablet and capsule forms were not that popular among them [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The attitude of the consumer toward a product can be divided into three components: (1) the cognitive component which defines the beliefs of consumer toward a product, (2) the affective component which defines the feelings or emotions of consumers toward the product obtained from effective experience and (3) the behavioral component which defines the probability that the individual will behave in a specific way (Schiffman and Kanuk, 2009). Carvalho et al (2014) conducted a study on the attitude of consumers toward probiotic products in the Vicosa city of Brazil with a validated questionnaire. The results indicated that there is a need for more explanatory labels stating Brazilian legislation and also need for campaigns to promote awareness of the health benefits of probiotic.…”
Section: Literature Reviewmentioning
confidence: 99%